Periodic acid–Schiff staining demonstrates fungi in chronic anterior blepharitis - Dadaci, Z (Eye (Lond), 2015)
PURPOSE: To evaluate the presence of fungi in patients with chronic anterior blepharitis with periodic acid–Schiff (PAS) staining of the eyelashes in addition to the conventional methods of fungal cultures and direct microscopy. METHODS: Nineteen patients with chronic anterior blepharitis of seborrheic or mixed seborrheic/staphylococcal type and 11 healthy age- and sex-matched controls were included in this prospective, nonrandomized, cross-sectional study. Blepharitis was diagnosed based on clinical evidence of greasy scales between the cilia, lid margin erythema, conjunctival hyperemia, telangiectasia, thickening, or irregularity of the eyelid margins by slit-lamp biomicroscopy. Eyelash samples were obtained by epilation with a sterile forceps and evaluated with PAS staining, fungal cultures, and direct microscopy. RESULTS: We demonstrated fungal elements with PAS staining in 79% of the blepharitis group (hyphae and/or spores) and 18% of the control group. The difference was statistically significant (P=0.002). Four patients in the blepharitis group (21%) had positive cultures for fungi. The isolated fungi were Penicillium species (2 cases), Candida species (1 case), and Trichophyton verrucosum (1 case). Direct microscopic examination revealed Demodex mites in 42.1% of the blepharitis group. No culture growth or Demodex mites were observed in the control group. CONCLUSIONS: We have shown fungi with PAS staining in the majority of patients with chronic anterior blepharitis. Further controlled studies are necessary to clarify the role of fungi in the etiopathogenesis of blepharitis.